Public debt in an OLG model with imperfect competition: long-run effects of austerity programs and changes in the growth rate - Peter Skott; Soon Ryoo (University of Massachusetts, Department of Economics, 2013)
We show that (i) dynamic inefficiency may be empirically relevant in a modified Diamond model with imperfect competition, (ii) if fiscal policy is used to avoid inefficiency and maintain an optimal capital intensity, the required debt ratio will be inversely related to the growth rate, and (iii) austerity policies reductions in government consumption and entitlement programs for the old generation raise the required debt ratio.
Keywords: E62; E22; 330; Public debt; dynamic efficiency; growth effects; austerity